Examining the Roles of Historical and Digital Jesus in Counseling, Spiritual Growth, and Ethics - Zalukhu, Amirrudin; Ester, Ester (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract:This study examines the roles of Jesus as both a historical and digital figure in the context of spiritual counseling, spiritual growth, and ethical implications in the age of artificial intelligence (AI). In a world increasingly shaped by technology, the presence of Jesus in digital form offers the potential to enrich the spiritual experiences of Christians. This research identifies how technological applications, such as AI-based counseling platforms and spiritual chatbots, can bring individuals closer to Jesus as a counselor and savior. Additionally, the study explores ethical challenges related to data privacy, the limitations of AI in understanding the depth of human spirituality, and the alignment between technology and the teachings of Christ. Using a qualitative approach through a literature review, this article provides insights into how technology can support or even replace deeper spiritual experiences, while still preserving Christian values. The implications of this study are significant for churches and spiritual organizations in integrating technology with ethics that honor spiritual values